PENGARUH KEPRIBADIAN DAN MOTIVASI TERHADAP PERILAKU CARING PERAWAT DI RSUD KABUPATEN KAUR - Yogi Rahmatin Hasanah; Sigit - Nugroho; Praningrum - - (Student Journal of Business and Management, 2021)
The research objectives were (1) to determine the effect of personality on nurses 'caring behavior (2) to determine the effect of work motivation on nurses' caring behavior. This type of research is quantitative research, the population is all nurses in Kaur Hospital, amounting to 54 people, the sample was taken by the census method as many as a total of a population of 54 people. The data were collected using an online questionnaire survey and analyzed using multiple linear regression analysis, determination test and hypothesis testing. The results showed that personality had a positive and significant effect on the caring behavior of nurses at Kaur District Hospital. This means that the better the nurse's personality, the higher the caring behavior. Conversely, the worse the nurse's personality, the lower the caring behavior. Motivation has a positive and significant effect on the caring behavior of nurses at the Kaur District Hospital. This means that the higher the nurse's motivation, the higher the caring behavior. Conversely, the lower the nurse's motivation, the lower the caring behavior. The suggestion of this research is that the Kaur District Regional Hospital can hold soft skill training for all nurses at the Kaur Regency Regional Hospital on an ongoing basis. The training is expected to grow and improve the positive personality of nurses so that they are skilled in applying care Then increase the motivation of nurses through a reward system, for example displaying photos of beautiful nurses per month, providing rewards in the form of materials, training and so on, so that these driving factors can further increase the motivation of nurses to behave caring.